Strategy to Improve Business Performance of Palm Oil Sector in Merangkai Village, Dayun District, Siak Regency: Impact of Digital Marketing and Marketing Strategy - Lie Othman; Meyzi Heriyanto; Kasmirudin Kasmirudin; Mashur Fadli; Hussein Al Muhtadeebillah; Mandataris Mandataris (Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to measure the influence of digital marketing and marketing strategies in improving the business performance strategy of the palm oil sector in Merangkai Village, Dayun District, Siak Regency. The study used a quantitative approach where primary data was collected through a survey of 35 respondents, and the Partial Least Square (PLS) statistical technique was used to process the data. The study's results confirmed that digital marketing had no significant influence on the business performance of the palm oil sector. The marketing strategy variable impacts the business performance of the palm oil sector. Still, some other factors or variables influence the business performance variable of the palm oil sector in Merangkai Village, Dayun District, Siak Regency.